Thalathata Qurū dalam Perspektif Modern: Integrasi Yurisprudensi Islam dan Teknologi Ultrasonografi - Jannah, Miftahul; Afifi, Mohammad (Moderasi : Journal of Islamic Studies, 2024)
This study examines the Quranic term Thalathata Qurū and its associated concept of iddah, focusing on their classical interpretations and relevance in contemporary contexts. The research aims to explore how traditional Islamic jurisprudence can adapt to modern advancements, such as ultrasonography, while preserving the spiritual and ethical essence of Quranic mandates. Employing a multidimensional methodology, the study integrates textual, contextual, and comparative analyses to provide a holistic understanding of the subject. The findings reveal that while ultrasonography offers precise physiological assessments, it cannot substitute the broader spiritual and social functions of iddah. The study highlights the role of ijtihād and maqāṣid al-sharī’ah in reconciling traditional practices with modern realities, emphasizing the adaptability of Islamic jurisprudence. Additionally, it underscores the importance of interdisciplinary collaboration in contextualizing Quranic principles to address contemporary challenges. This research contributes to the discourse on integrating faith and technology by offering a framework for harmonizing Quranic teachings with scientific progress. It reaffirms the significance of Thalathata Qurū as a multifaceted concept that balances tradition and modernity, providing insights for addressing similar intersections of religion and science in Islamic jurisprudence. Future studies could further explore gender-sensitive interpretations and comparative analyses across religious traditions. Keywords: Thalathata Qurū, iddah, Islamic jurisprudence, ultrasonography, maqāṣid al-sharī’ah, ijtihād, interdisciplinary collaboration